Da criação à apresentação de propostas: movimento rítmico interdisciplinar desvelado na linguagem - Syrgiannis, Christine (2013)
the rhythmic movement evolves from the creation to the presentation of proposals unveiled in language, in the light of Interdisciplinarity. The object of the research is the professional performance of the researcher while promoting personal development through the English or Portuguese language for the creation of innovative proficient proposals. The movement will be explicited weaving the theory of Interdisciplinarity with the professional praxis of the researcher, involving the 12 shades of the movement, and key perceptions of this experience: the epistemological, praxiological and ontological aspects involved. The work reveals the pre requisites for this spyral movement of creation to occur. Temporalities and the interdisciplinar professional way of regarding the Being as full of possibilities in the Knowing and Doing are essential to activate the spyral of creation. When one opens to perceptions on a topic and registers them through words, one collects invaluable raw material. The approach to the topic, just like the anthropological method of looking in layers follows with the correlation of words, and detection of the meaning of the correlations. They constitute the different aspects of the topic and can, now, be expressed in sentenced. The definition of the proposal follows, by selecting the aspects, which will, like branches, compose the tree of the topic. In group, or individually the proposal is rehearsed aiming at adjusting it or confirming it. With clarity and harmony the process follows in a specific way to the achievement with self realization. Presentation of a proficient proposal is the result of the interdisciplinary rhythmic movement born in the being and unveiled in the language. Consciousness of the Being emerges, as a gift in continuous expansion